Working with families for inclusive education - Sobsey, Richard; Scorgie, Kate (International perspectives on inclusive education ;, 2017)
This book explores personal, family and theoretical constructions of inclusion and offers evidence-based strategies and resources to foster parent-professional, home-school collaborative partnerships. It explores working with families to secure identity, opportunity and belonging within school settings and beyond. It does so by means of a rich international blend of scholarly articles and personal reflections.The first section examines personal, family, and theoretical perspectives on ways in which existing systems and structures define and influence inclusion of persons with disability and their families in school and workplace settings. It invites reflection on how we might come together to create more inclusive communities through mutual understanding and valuing. Section two presents a number of evidence-based practices, strategies, and resources that can serve to guide family members and professionals as they work together to build collaborative partnerships and inclusive school communities from preschool through transition to post-secondary and vocational settings.This book invites us to deeper understandings of collaboration, to engage reflection from diverse perspectives. It reminds us that at some level we are all navigating identity, opportunity and belonging; that each of us needs those who challenge us to see beyond our assumptions, whose ideas shape and sharpen our own.